Refusal towards vaccination: a survey among Malay parents - Mohamad Diah, Nurazzura; Samsudin, Suhaiza; Rehman, Adeela; Sedu, Nerawi (Zes Rokman Resources, 2019)
Vaccination is a preventive solution for children to protect them from infectious diseases. Although it is good immunization for children, some parents are reluctant about immunizing their children. The study attempts to identify the socio-cultural determinants of parental refusal for vaccination which may have influenced the uptake of vaccination. This study employed a survey method. A sample of 80 parents including both mothers and fathers who have children between the ages of one to 12 years old were recruited. The participants were selected via the random sampling technique. The questionnaire was distributed through email and on social media. Data were analyzed using SPSS. The results indicate that 58% of parents refused to vaccinate their children. Although parents are aware of the importance of vaccines, they refused to adopt them due to the perception that vaccination is unhygienic in nature and is considered unhealthy for their children. They also believed that other preventive methods are better than vaccination. The findings also illustrate significant positive correlation between parents’ educational level and their attitude towards vaccine refusal.